Comparison of the inhibition potential of parthenolide and micheliolide on various UDP-glucuronosyltransferase isoforms. (3rd October 2019) - Gao, Wei-Feng; Li, Yi-Xuan; Zhang, Wei-Hua; Tao, Ran; Yin, Ting-Ting; Wang, Yi-Jia; Liu, Li-Na; Fu, Zhi-Wei; Li, Sai-Nan; Liu, Nai-Rong; Zhang, Heng; Liu, Guang; et al.
Abstract: Parthenolide (PTL) and micheliolide (MCL) are sesquiterpene lactones with similar structures, and both of them have been reported to exhibit multiple biochemical and pharmacological activities. This study aims to investigate the inhibition of these two compounds on the activity of UDP-glucuronosyltransferases (UGTs). In vitro incubation mixture for recombinant UGTs-catalyzed glucuronidation metabolism of 4-methylumbelliferone (4-MU) was utilized to investigate the inhibition potential. Inhibition kinetics (including inhibition type and parameters) were determined, and in silico docking was employed to elucidate the inhibition difference between PTL and MCL on UGT1A1. MCL showed no inhibition toward all the UGT isoforms, and PTL showed strong inhibition toward UGT1A1. The half-maximal inhibitory concentration (IC50 ) of PTL on the activity of UGT1A1 was determined to be 64.4 μM. Inhibition kinetics determination showed that PTL exerted noncompetitive inhibition toward UGT1A1, and the inhibition kinetic constant ( K i ) was determined to be 12.1 μM. In silico docking method has been employed to show that hydrogen bonds between PTL and the activity cavity of UGT1A1 contributed to the stronger inhibition of PTL on the activity of UGT1A1 than MCL. In conclusion, PTL can more easily induce drug–drug interaction (DDI) with clinical drugs mainly undergoing UGT1A1-catalyzed glucuronidation.